Effect Of Different Feeding Systems On Growth Performance And Carcass Traits Of Growing And Finishing Pigs - Ramesh, V.; Edwin, S.C.; Murugan, M.; kumar , S. Vasantha (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was carried out with twenty four Large White Yorkshire weaned piglets to find out the effect of different feeding regimes on growth performance of pigs. The piglets at weaning were randomly divided into four groups of six each. The first group (T1 ) fed with 100 per cent concentrate and the same was replaced on DM basis with hostel food waste at 50 per cent level (T2) , the third group (T3 ) 50 % concentrate with 25 % swill and 25 % Hedge Lucerne and the fourth group (T4) was fed with 50 % swill, 25 % concentrate and 25 % Hedge Lucerne . A significantly (P
Keywords: Feeding systems; Pig; Growth; Carcass traits